PROTECTING GROUPS FOR ORGANIC SYNTHESIS - Asmaa Najeeb Ahmad Saleh; Khadija Nasser Mohammed Noori; Saja Huusin Ali Sulamin; Ghufran Kadhum Abed Hasan; Qahtan Adnan Jassim Mohammad (Journal of Medical Genetics and Clinical Biology, 2024)
A protecting group (English protecting group - therefore often referred to as common abbreviation in formula schemes PG) is in chemistry a substituent which, during a more complicated, multi-step chemical synthesis in a molecule is introduced to a specific functional group to protect temporarily and so an undesirable reaction to prevent this group. After the desired reaction has been carried out elsewhere on the molecule, the protective group is split off again. For many functional groups several possible protective groups are known which differ in their stability and the conditions for their cleavage. In the synthesis of special classes of compounds with repeating functional groups - usually biomolecules such as peptides, oligosaccharides or nucleotides - standard sets of protective groups have become established. Protecting groups have become an important tool in the synthesis of complex compounds today. The requirements for a protection group are quite high. This includes that it can be introduced specifically to a functional group with very good vield and that it must also be able to be split off yield and that it must also be able to be split off again under mild conditions. It should be possible to standardize the reaction conditions for both steps. In addition, the protective group must be stable under as many reaction conditions as possible. If possible, the resulting reaction products should be easily separable, and optimally the protective group reagent is also inexpensive. The broader the experience with a protective group, the better the predictability of the reactivity of the protective group.